Effects of the minimum wage on US county labor markets - Otterby, Dawn; Crawley, Andrew; Gabe, Todd (Regional science policy & practice, 2024)
This study investigates the impacts of the minimum wage on U.S. regional labor markets. Using ten years of county-level data, we examine the relationship between the minimum wage and several key components of the labor market. Following past research, the number of people in the labor force is used to measure labor supply, but—as an extension to the literature—job postings data are included to measure labor demand. Consistent with previous studies, we find a positive relationship between labor force participation and a county’s minimum wage. The results are mixed, however, when examining the effects of the minimum wage on job postings.